REAKSI INVESTOR TERHADAP NILAI TAMBAH EKONOMI - ELI ROHMAWATI; Andry Irwanto (Jurnal Ekonomi dan Bisnis Airlangga, 2018)
Introduction: This study aims to analyze investors' reactions to economic value added (EVA). Methods: This research uses quantitative methods. The research data was obtained from the Indonesia Stock Exchange and the annual financial reports of sample companies in the 2009-2012 period. Manufacturing companies are used in this study with a sample company of 34 companies. Results: The results of the study concluded that there was significant investor reaction around the date of the announcement of financial statements on companies that had positive economic value added (EVA) and significantly there were investors' reactions around the date of the announcement of financial statements on companies with negative economic value added (EVA). Conclusion and suggestion: Further researchers are expected to add other industrial sectors that can apply the EVA concept, and real data in determining the cost of debt (COD)